Hubungan Fasilitas Workshop terhadap Hasil Belajar pada Mata Pelajaran Teknik Frais Siswa Kelas XI Teknik Pemesinan SMK Negeri 1 Tanjung Raya - Robert, Julio; Erizon, Nelvi; K, Arwizet; Yuvenda, Dori (Al-DYAS, 2024)
Vocational High School (SMK) which is a school that educates students with professional knowledge and skills as well as talents and interests to prepare skilled workers in accordance with the needs of the business world and industry. Therefore, in the learning process, practicum facilities in the workshop play an important role in determining the success of students to learn effectively so as to achieve the desired learning outcomes. This study aims to determine the relationship between the completeness of Workshop facilities and student learning outcomes in grade XI students majoring in Mechanical Engineering at SMK Negeri 1 Tanjung Raya. This study uses a type of correlational quantitative research with a population of 60 students. The questionnaire with 35 items was used as a measuring tool, the results of the study showed a significant relationship between the learning outcomes of milling machining techniques of grade XI students of SMK Negeri 1 Tanjung Raya and the completeness of workshop facilities where R calculated (0.603) > R table (0.254). The completeness of workshop facilities contributed 36.3% to the success of milling machining engineering learning for grade XI students of SMK Negeri 1 Tanjung Raya and another 63.7% was influenced by other factors.